Modification of Human Islet Preparation: An Effective Approach to Improve Graft Outcome After Islet Transplantation? - Zhao, M.; Choudhary, P.; Srinivasan, P.; Tang, H.; Heaton, N.; Fung, M.; Barthel, A.; Bornstein, S. R.; Amiel, S. A.; Huang, G. C. (Hormone and Metabolic Research, 2015)
Revascularisation of transplanted islets is an essential prerequisite for graft survival and function. However, current islet isolation procedures deprive the islets of endothelial tubulets. This may have a detrimental effect on the revascularisation process of islets following transplantation. We hypothesise that modification of the isolation procedure that preserves islet endothelial vessels may improve the islet revascularisation process following transplantation. Here, we present a modified islet isolation method by which a substantial amount of endothelial cells still attached to the islets could be preserved. The islets with preserved endothelial cells isolated by this method were revascularised within 3 days, not observed in islets isolated by standard methods. Further, we observed that grafts of islets isolated by standard methods had more patches of dead tissue than islet grafts obtained by the modified method, indicating that attached endothelial cells may play an important role in the islet revascularisation process and potentially help to improve the transplantation outcome.
Keywords: human islet; transplantation; endothelium cells; revascularisation